Does antennal sensilla pattern of different populations of Triatoma maculata (Hemiptera: Reduviidae) reveal phenotypic variability? - Nogueira Müller, Josiane (2019)
Background: In Brazil, Triatoma maculata is only found in the State of Roraima and is a vector of Trypanosoma cruzi, the etiological agent of Chagas disease. It occurs in wild, peridomestic and domestic habitats, with an urban infestation in Boa Vista, the capital of this Brazilian state. The aim of this study was to assess the morphological variability of the T. maculata antennal phenotype in three populations of Roraima State, using the antennal sensilla pattern analyzed under optical microscopy. Methods: The number and distribution of four antennal sensilla types (bristles, thin and thick walled trichoidea, and basiconic) of three Brazilian populations of T. maculata from Roraima State were compared. Univariate and multivariate analyses were performed. Results: The antenna of T. maculata presented the four types of sensilla. According to the density and distribution of the antennal sensilla characteristics, the multivariate analyses showed that the laboratory population is morphologically structured. Urban specimens showed a pronounced phenotypic variability. The main differences were observed in the pedicel segment, and between males and females. Conclusions: We determined the antennal phenotype in three Roraima populations of T. maculata. These results support the idea that the patterns of antennal sensilla are sensitive markers for distinct populations in the Triatominae. The infestations of T. maculata in different habitats reinforces the ability of this vector to become adapted to a variety of environments, which, could have eco-epidemiological implications for the T. cruzi transmission that are still not well understood.